Pengaruh Komposisi Cairan Additif Terhadap Kuat Tekan Dan Daya Infiltrasi dalam Pengembangan Pervious Paving Block Ramah Lingkungan - Afrian Wira Wardhana; Amirin Kusmiran; Andy Tirta (Jurnal Metalurgi dan Material Indonesia, 2018)
Analysis of compressive strength and infiltration pervious paving was performed by falling head method at 7, 14, and 28 days with variation of additive composition by 70 ml, 140 ml, 210 ml, and 280 ml. The addition of lignosulfonat acid additive in the pervious paving making mixture affects the mechanical properties of pervious paving such as compressive strength, permeability and cement bonding time. The results showed the most significant increase in compressive strength occurred during baseline time. Addition of lignosulfonat acid additive affects the acceleration of hydration power of cement up to 2.6 times of normal binding time. Pervious paving infiltration test results showed that the higher content of additive contained, the smaller the permeability. So we get the optimum composition of 140 ml additive substances with a compressive strength of 19.4 MPa and permeability of 0.367 cm / sec.